Plasma Surface Modified Polytetrafluoroethylene Grafted Nanolayers and Complexes Therefrom - Turmanova, Sevdalina Chr (International Journal of Chemistry and Materials Research, 2014)
Metal complexes of copolymers based on poly(acrylic acid), poly(4-vinylpyridine) and poly(1-vinylimidazole) plasma grafted onto films of poly(tetrafluoroethene) were prepared by complex formation with solutions of salts of FeCl3.6H2O, CuCl2.2H2O, CoCl2.6H2O, VOSO4.5H2O and Na2MoO4.2H2O at room temperature. The introduction of metal ions was found to depend mainly on the degree of grafting of acrylic acid, 4-vinylpyridine and 1-vinylimidazole and was from 1.1 tо 6.5 mg metal ion/g polymer carrier. The studies carried out by IR spectroscopy, Moessbauer spectroscopy and electron paramagnetic resonance proved the preparation of metal complexes.